Outcomes of regenerative treatment with rhPDGF‐BB and rhFGF‐2 for periodontal intra‐bony defects: a systematic review and meta‐analysis. (20th February 2015) - Khoshkam, Vahid; Chan, Hsun‐Liang; Lin, Guo‐Hao; Mailoa, James; Giannobile, William V.; Wang, Hom‐Lay; Oh, Tae‐Ju
Abstract Background The aim was to evaluate the effects of recombinant human platelet‐derived growth factor‐BB (rhPDGF‐BB) and recombinant human fibroblast growth factor‐2 (rhFGF‐2) on treating periodontal intra‐bony defects, compared to the control (carrier alone). Methods Electronic and hand searches were performed to identify eligible studies. The weighed mean differences of linear defect fill (LDF), probing depth (PD) reduction, clinical attachment level (CAL) gain and gingival recession (GR) were calculated using random effect meta‐analysis. Results The searches yielded 1018 articles, of which seven studies were included. Only one included study was considered at low risk of bias. The outcomes that reached statistical significance in comparison to carriers alone included: LDF (0.95 mm, 95% CI: 0.62–1.28 mm or 20.17%, 95% CI: 11.81–28.54%) and CAL gain (0.34 mm, 95% CI: 0.03–0.65 mm) for PDGF, and LDF (21.22%, 95% CI: 5.82–36.61%) for FGF‐2. Conclusions Within the limits of this review, rhPDGF‐BB demonstrated significantly more LDF and CAL gain; rhFGF‐2 resulted in significantly higher percentage of LDF.